Pharmacological Mechanisms of Active Constituents from Traditional Chinese Medicine for Vitiligo Treatment - Adina Hamiti; Yingying Geng; Pengfei Huang; Jinghui Xie; Tingting Cui (Pharmaceuticals, 2026)
Vitiligo is a chronic acquired depigmenting disorder characterized by progressive melanocyte loss. Its pathogenesis involves a multifactorial interplay among oxidative stress, impaired melanocyte regeneration, immune-mediated cytotoxicity, and neuroendocrine dysregulation. In recent years, traditional Chinese medicine (TCM)-derived active ingredients have attracted increasing research interest as potential interventions for vitiligo, although most isolated compounds remain at the preclinical stage. This review summarizes pharmacological and natural compounds applied in vitiligo treatment and highlights their regulatory mechanisms on core pathogenic modules. A comprehensive analysis of natural and semisynthetic active ingredients is provided, covering their preclinical and clinical evidence, mechanisms of action, and therapeutic relevance. Multiple ingredients, including baicalein, quercetin, curcumin, paeoniflorin, kaempferol, glycyrrhizin, and epigallocatechin-3-gallate (EGCG), have demonstrated antioxidant, anti-inflammatory, immunomodulatory, and neuroprotective effects that are involved in the pathogenesis of vitiligo. Some TCM-derived interventions, such as Ginkgo biloba L. extract and compound glycyrrhizin, have been evaluated clinically, whereas most isolated active compounds, including baicalein and quercetin, remain at the preclinical stage. Overall, TCM-derived active ingredients represent a promising therapeutic strategy for vitiligo. However, continued translational and clinical research is still required to optimize formulations, dosing regimens, and safety profiles, thereby facilitating their integration into routine clinical practice.